The role of IT tools supporting the use of abstract thinking in creating intellectual capital perceived from the perspective of the employer - Stępniak, Cezary; Chluski, Andrzej; Závadská, Zuzana (Rola narzędzi IT wspierających wykorzystanie abstrakcyjnego myślenia w kreowaniu kapitału intelektualnego postrzegana z perspektywy pracodawcy, 2019)
The article is devoted to the subject of building the intellectual capital of enterprises using the competences of employees regarding their ability to use methods based on abstract thinking. The starting point was the question whether the contemporary employer needs employees who can mainly perform real tasks or are able to apply abstract thinking to solve problems occurring in the enterprise. Against this background, it was also tried to determine what role IT tools can play in this situation. For the purposes of the article, research was carried out with a group of employers who spoke about the needs of their companies in the area of creating their intellectual capital, demand for employee competences in the field of abstract thinking and their creativity, and also to determine what role ICT tools can play
Informatyka Ekonomiczna = Business Informatics, 2019, Nr 2 (52), s. 101-113
Keywords: intellectual capital; abstract thinking; information technology; kapitał intelektualny; myślenie abstrakcyjne; technologie informacyjne